Effect of ammonia fuel fraction on the exergetic performance of a gas turbine. (July 2018) - Ayaz, S. Kagan; Altuntas, Onder; Caliskan, Hakan
Abstract: Decreasing of fossil fuels and increasing global warming lead researchers to find cheap and environmentally friendly alternative energy sources. In this regard, ammonia (NH3 ) is a widely used feedstock. This carbon free fuel can be combusted in gas turbines or internal combustion engines, producing only nitrogen and water vapor. Nevertheless, ammonia is hard to burn because of low laminar burning velocity. In this paper, the effect of ammonia fuel fraction on the exergetic performance of a Turbec T100 micro gas turbine is investigated. Three different fuels are considered to operate the gas turbine: (i) natural gas (100%CH4 ), (ii) natural gas blend with %10 ammonia fraction (10%CH4 -90%NH3 ) and (iii) natural gas blend with %20 ammonia fraction (20%CH4 -80%NH3 ). The operating data of the micro turbine is obtained from the literature and the micro turbine is modelled with EBSILON software. It is found that %20 ammonia fraction is more environmentally benign compared to %10 ammonia fraction and natural gas fuels. The exergetic sustainability indicators are also determined as 3.168, 2.864 and 3.7 for the natural gas, 10% ammonia blend and 20% ammonia blend combustions, respectively. So, the controlling of ammonia fraction is important to sustain exergy efficiency of the micro turbine. More detailed combustion and environmental analyses are also necessary for better evaluation of environmental effects on the micro turbine during ammonia and natural gas combustions.